Program Komunikasi Kreatif untuk Meningkatkan Partisipasi Pemilahan Sampah di Sekolah Kewilayahan Maleer Bandung - Rizki Pratami, Nadia; Kusdiantini, Andini; Usviany, Veny; Yudiarti, Diena; Sudrajat, Jajat; Sanny, M. Yusuf (LPPM Politeknik Piksi Ganesha, 2024)
Creative communication programs are an innovative approach to increasing awareness and participation in activities that support environmental sustainability. This Community Service initiative aims to develop and implement a creative communication program to enhance student participation in waste segregation activities at Maleer Regional School, Bandung. The program was designed based on a needs analysis involving students, teachers, and school stakeholders, utilizing visual and audio media as well as interactive activities to deliver educational messages about the importance of waste segregation. The method employed is a participatory approach, involving students in the planning, implementation, and evaluation processes of the program. Activities include creating educational posters, campaign videos, creative recycling workshops, and waste segregation competitions. The program outcomes demonstrated a significant increase in students' understanding of waste segregation concepts and their motivation to actively participate in these activities. The program's success is evidenced by the reduction in mixed waste and the improved quality and quantity of recycled waste at the school. By adopting a creative communication approach, this program effectively changed students' behavior to become more environmentally conscious, contributing to a cleaner and healthier school environment. The findings of this initiative recommend the application of similar approaches in other schools as part of a collective effort to support sustainable waste management and raise environmental awareness among the younger generation.